2023
DOI: 10.2147/idr.s404171
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Perceptions of Tuberculosis in Indonesia: A Multi-Center Cross-Sectional Study

Abstract: Introduction Tuberculosis (TB) is still a persistent health challenge in Indonesia and ranks high on the list of factors causing morbidity and mortality. Improving knowledge, attitudes, and perceptions (KAP) of the general community about TB can help to control the disease. Purpose This study aimed to examine the KAP about TB in Indonesian society and investigate their sociodemographic determinants. Participants and Methods An online cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…In addition, the results regarding academic levels align with our results, as we found that participants from the first two academic years were less likely to have good knowledge when compared to higher academic levels (p< 0.001). Other reports from Bhutan and Bangladesh [22,23] also concur with our findings. This finding might be attributed to the fact that young people are open to receiving information.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the results regarding academic levels align with our results, as we found that participants from the first two academic years were less likely to have good knowledge when compared to higher academic levels (p< 0.001). Other reports from Bhutan and Bangladesh [22,23] also concur with our findings. This finding might be attributed to the fact that young people are open to receiving information.…”
Section: Discussionsupporting
confidence: 92%
“…11 About the qualification of tuberculosis prevention and treatment information among tuberculosis patients, the univariate analysis showed that there were no significant differences in different genders, age groups, ethnicities, occupations, and chronic diseases (P≥0.05), while there were statistically significant differences between different education levels, current residence types, and monthly income levels, which were consistent with the results of other studies. 12,13 The ≥65 age group had lower total knowledge awareness rates in the total population, males, and females than the control group. With the increase of age, the awareness rate tends to decline, which may be due to the lack of understanding and mastery of health knowledge among the elderly.…”
Section: Discussionmentioning
confidence: 89%
“…Hasil penelitian terkait persepsi pekerja migran latin di Amerika Serikat didapatkan bahwa pekerja dengan tingkat pendidikan yang lebih rendah, cenderung memiliki persepsi yang kurang tepat terkait tuberkulosis (Eggerth, et al 2018). Karyawan berpendidikan tinggi cenderung menerima intervensi terkait tuberkulosis di tempat kerja karena berpikir Tuberkulosis akan berdampak pada pemutusan hubungan kerja, pemotongan gaji, dan tindakan sejenis yang tidak akan menimpa (Eggerth et al, 2018;Kaaffah et al, 2023), seperti terlihat pada Gambar 1 dan Gambar 2. PKM juga memberikan data secara tertulis kepada pihak divisi HRD.…”
Section: Persepsi Terkait Tuberkulosis Pada Karyawanunclassified